Knowledge Sharing and Innovative Work Behaviors of Supervisory-Level Employees in a Packaging Manufacturing Company: Knowledge Sharing and Innovative Work Behaviors of Supervisory-Level Employees in a Packaging Manufacturing Company - Angkavichai, Bhakin; Akkawanitcha, Chuanchuen (RATANABUTH JOURNAL, 2023)
The objective of this research was to study the Factors affecting Knowledge Sharing and Innovative Work Behavior model and verify the consistency of the developed model with empirical data. The quantitative research method is employed. The sample group are 350 supervisory-level employees at Thai Containers Group Co., Ltd.. The questionnaire was employed as research instrument. Data is analyzed by the structural equation model (SEM). The results of analyzed influence path model showed that Subjective Norm, Trust and Leader Member Exchange have a positive influence on Knowledge Sharing, and the Leader Member Exchange and Knowledge Sharing have a positive influence on the Innovative Work Behavior. The developed influence path model is consistent with the empirical data, the Chi-Square value are 364.199, with statistical significance at 0.06, The Chi-Square correlation are 1.194, and Comparative Fit Index (CFI) are 0.993, Goodness of Fit Index (GFI) are 0.944, Normed Fit Index (NFI) are 0.964, Root Mean Square Error of Approximation (RMSEA) are 0.024 and Root Mean Residual (RMR) are 0.018. The factors that have the most influence on Knowledge Sharing are Trust, Leader Member Exchange and Subjective Norm.